Content, formats and licensing of datasets from autonomous communities: Value generation, sustainability and proposals for improvement - Curto-Rodríguez, Ricardo; Marcos-Sánchez, Rafael; Ferrández, Daniel (International Journal of Information Management Data Insights, 2026)
Open government data (OGD) initiatives, established at all levels of public administration and globally, have significant potential for value generation. However, their actual implementation often reveals significant shortcomings that hinder their potential for value creation. This study addresses a critical gap in the literature by evaluating the design of OGD policies in Spain, focusing specifically on the industrial sector at the autonomous community level. The research assesses the available data's content, formats, and licensing through a population-based analysis of all datasets labeled under the “industry” category across the 17 Spanish autonomous communities. The findings reveal a fragmented and inconsistent landscape: of over 46,000 datasets published by autonomous community governments, only 532 were initially labeled as industry-related, and after a rigorous selection process—removing duplicates, outdated records, and mislabeling entries—only 316 were deemed valid. The study highlights a predominance of non-reusable formats such as HTML and a lack of standardisation in the categorization of information. While most datasets use open licenses (mainly Creative Commons BY), the variability in download options and formats limits their automated processing and reuse. These results underscore the need for standardization criteria, improved data quality, and strategic alignment of OGD initiatives with sectoral priorities such as industrial competitiveness and sustainability. The paper concludes with four contributions to enhance coherence, usability, and impact of open industrial data, aiming to support OGD policymaking and foster innovation ecosystems at the autonomous community level.
Keywords: autonomous communities; open government data; Spain; industry; public information